Association of food security, body mass index, micronutrient adequacy and adherence to Alternative Healthy Eating Index 2010 among Iranian households. Issue 5 (15th October 2020) - Moosavian, Seyedeh Parisa; Feizi, Awat; Esmaillzadeh, Ahmad; Azadbakht, Leila
Abstract : Purpose: There is limited knowledge about the association of food insecurity and dietary quality among the Iranian households. The purpose of this study is to determine diet quality among the Iranian households and to investigate whether dietary quality is associated with food security status in this population. Design/methodology/approach: The 18-item household food security questionnaire was administered to 200 households from different parts of Isfahan, Iran. Households were selected by two-stage cluster randomized sampling. Households were categorized into four groups based on their score on the questionnaire; food secure (total score 0), mild food insecure (total score 1–2), moderate food insecure (total score 3–7) and severe food insecure (total score 8–18). In the second stage of the study, 25 households were selected from each food security status group to evaluate the micronutrient adequacy and assess the adherence to Alternative Healthy Eating Index 2010 (AHEI-2010). Findings: Food-secure households had higher adherence to the AHEI-2010 than food-insecure households ( p < 0.001). Food-secure households consistently achieved higher value of the nutrient adequacy ratio for most of the micronutrients than food-insecure households, with the greatest differences seen for zinc ( p < 0.001) in households (father, mother and first child), vitamin D ( p < 0.001), vitamin A (father: p = 0.05, mother: p = 0.04), calcium ( p < 0.001) and iron (father: p = 0.02, mother: p < 0.001) in mother and father. Originality/value: Low dietary quality was associated with food insecurity. Food-secure households had higher micronutrient adequacy ratio for most of the nutrients.